Low and atmospheric plasma polymerisation of nanocoatings for bio-applications. Issue 2 (1st June 2015) - Pulpytel, Jerome; Arefi-Khonsari, Farzaneh; Bhatt, Sudhir
Abstract : There exists an abundant literature on polymers used for biomedical applications. However, the research described in this article deals with the plasma (co)polymerisation of different organic precursors for surface modifications of a variety of substrates in order to tailor the physico-chemical properties of the substrates for tuneable biomolecule–surface interactions. The major part of the work presented focuses on the low-pressure inductively excited plasma-enhanced chemical vapour deposition of organic precursors for the functionalisations of material. In the second part of the article, an open-air custom-made atmospheric-pressure dielectric barrier discharge (DBD) plasma jet is discussed for the anti-fouling applications. This special focus aims to elaborate the state of the art of different low and atmospheric pressure plasma-deposited polymers for anti-fouling applications, cell–surface interactions and tissue engineering applications.